2019
DOI: 10.18845/tm.v32i10.4876
|View full text |Cite
|
Sign up to set email alerts
|

Agua para consumo humano y saneamiento en Centros Educativos de Costa Rica al año 2017

Abstract: Este estudio retrospectivo tiene como objetivo principal “estimar la cobertura del agua para consumo humano y saneamiento en aguas residuales, en los centros educativos de Costa Rica al año 2017, con el propósito de establecer la línea base y las metas para la Agenda 2030, en el marco de los Objetivos de Desarrollo Sostenible”. Para su cumplimiento, la metodología consistió en el análisis de datos de acceso a agua por mecanismo de abastecimiento, mediante el aporte del Ministerio de Educación Pública con su do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The study design was described in some publications (24; 48.90%): descriptive (8; 16.32%) [30][31][32][33][34][35][36][37], cross-sectional or ecological (4; 8.16%) [38][39][40][41], documentary (3; 6.12%) [42][43][44], retrospective cohort [45,46], epidemiological [47,48], case study [49], action research [50], experience report [51], and quantitative-qualitative evaluative and mixedmethods research [52]. Other publications were reports regarding surveillance actions (14; 28.57%) [53][54][55][56][57][58][59][60][61][62][63][64][65][66].…”
Section: Characterization Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The study design was described in some publications (24; 48.90%): descriptive (8; 16.32%) [30][31][32][33][34][35][36][37], cross-sectional or ecological (4; 8.16%) [38][39][40][41], documentary (3; 6.12%) [42][43][44], retrospective cohort [45,46], epidemiological [47,48], case study [49], action research [50], experience report [51], and quantitative-qualitative evaluative and mixedmethods research [52]. Other publications were reports regarding surveillance actions (14; 28.57%) [53][54][55][56][57][58][59][60][61][62][63][64][65][66].…”
Section: Characterization Of Included Studiesmentioning
confidence: 99%
“…Surveillance actions assessing the coverage, quantity, and accessibility of drinking water for the population were poorly highlighted in studies conducted in Costa Rica [30,44], Brazil [35], and India [52]. Some studies revealed locations in which almost the entire population was supplied [30,44].…”
Section: Class 1 -Assessment Of Coverage Accessibility Quantity and D...mentioning
confidence: 99%
See 2 more Smart Citations
“…Reports describing water quality must be produced periodically by public health authorities, integrated into management and policy actions, and combined with better dissemination and communication among stakeholders [3,8]. The study design was described in some publications (24; 48.90%): descriptive (8; 16.32%) [29][30][31][32][33][34][35][36], cross-sectional or ecological (4; 8.16%) [37][38][39][40], documentary (3; 6.12%) [41][42][43], retrospective cohort [44,45], epidemiological [46,47], case study [48], action research [49], experience report [50], and quantitative-qualitative evaluative and mixed-methods research [51]. Other publications were reports regarding surveillance actions (14; 28.57%) [52][53][54][55][56][57][58][59][60][61][62][63][64][65].…”
Section: Characterization Of Included Studiesmentioning
confidence: 99%